Understanding the Anti-Diarrhoeal Properties of Incomptines A and B: Antibacterial Activity against Vibrio cholerae and Its Enterotoxin Inhibition - Fernando Calzada; Elihu Bautista; Sergio Hidalgo-Figueroa; Normand García-Hernández; Claudia Velázquez; Elizabeth Barbosa; Miguel Valdes; Jesús Iván Solares-Pascasio (MDPI AG, 2022)
Incomptines A (IA) and B (IB) are two sesquiterpene lactones with antiprotozoal, antibacterial, cytotoxic, antitumor, spermicidal, and phytotoxic properties. The antibacterial activity of IA and IB against bacteria causing diarrhoea have been reported; however, no information is available regarding their antibacterial activity on Vibrio cholerae. In this work, both compounds were evaluated for their anti-diarrhoeal potential using the bacterium V. cholerae, sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis on cholera toxin, and a cholera toxin-induced diarrhoea model in male Balb/c mice. In addition, a molecular docking study was carried out to understand the interaction of IA and IB with cholera toxin. In terms of antibacterial activity, IB was three times more active than IA on V. cholerae. In the case of SDS-PAGE analysis and the in silico study, IA was most effective, revealing its potential binding mode at a molecular level. In terms of anti-diarrhoeal activity, IA was 10 times more active than IB and racecadotril, an antisecretory drug used as positive control; the anti-diarrheal activity of IB was also closer than racecadotril. The results obtained from in vitro, in vivo, and computational studies on V. cholerae and cholera toxin support the potential of IA and IB as new anti-diarrhoeal compounds.